Stimulating satisfaction and loyalty: transformative behaviour and Muslim consumers - Mohamed, Naushad; Taheri, Babak; Farmaki, Anna; Olya, Hossein; Gannon, Martin Joseph (My University, 2020)
Purpose: This study aims to investigate the combinations of religiosity, cosmopolitanism and perceived destination image leading to satisfaction and loyalty amongst Muslim consumers within the Maldivian tourism and hospitality context. Design/methodology/approach: Using fuzzy-set qualitative comparative analysis (fsQCA), this study reveals that diverse combinations of religiosity, cosmopolitanism and destination image dimensions stimulate satisfaction and loyalty in Muslim consumers. Findings: Multiple recipes can be used to design compelling destinations that balance the desire for religiosity and cosmopolitanism characteristic of contemporary Muslim consumers. The results confirm the applicability of complexity theory in explaining Muslim consumer behaviour within the Islamic destination context. Practical implications: Several implications for the hospitality and tourism industry are drawn from the results, with suggestions for future research provided. Each fsQCA recipe identifies distinct suggestions to shape the design of destination attributes and hospitality offerings to stimulate consumer satisfaction and loyalty. Originality/value: Complexity theory was applied to assess the complex causal relationships among Muslim consumers’ religiosity, perceived destination image, cosmopolitanism, satisfaction and loyalty.
Keywords: Consumer behaviour; Cosmopolitanism; Destination image; Maldives; Religiosity